Demand for tobacco products in Bangladesh - Ahmed, Nasiruddin; Mozumder, Tanvir Ahmed; Hassan, Md. Tariq; Huque, Rumana (BMJ Journals, 2022)
This article was published in Tobacco Control [©2012 Published by 2021, BMJ Publishing Group Ltd.] and the definite version is available at: http://dx.doi.org/10.1136/tobaccocontrol-2020-056297 The Article's website is at: https://tobaccocontrol.bmj.com/content/early/2021/04/01/tobaccocontrol-2020-056297